Hydrocephalus Water on the Brain - Gürer, Bora (IntechOpen, 2018)
Hydrocephalus is a common manifestation of many diseases. Caring and treating a patient with hydrocephalus involve engagement and acquire a deep knowledge of anatomy, physiology, and technical details. Despite the technological developments, treatment of hydrocephalus is still a challenge for every neurological surgeon. The aim of this project is to provide a detailed and accessible information for every single discipline, not only for neurological surgeons, involved in the diagnosis and treatment of the patients with hydrocephalus.